2022
DOI: 10.3390/plants11212925
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tree Species and Size on Bark Browsing by Large Wild Herbivores

Abstract: Although an important part of the ecosystem, large wild herbivores (LWH), especially red deer (Cervus elaphus L.), cause significant damage to economically valuable timber in forests of Central Europe. Recent work has demonstrated that less valuable softwood broadleaved trees can act as “biological control” that helps reduce bark browsing on more valuable trees in a mixed stand. To better understand the factors that influence how much bark area and mass are removed by LWH from these broadleaved trees, we took … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…We assumed that very few bark-stripping damage occurred in plantations younger than 8 years old (the simulations started in stands 8 years old) in line with several studies (Vospernik, 2006;Jerina et al, 2008;Gill et al, 2000;Konôpka et al, 2022). At 8 years old, the mean tree diameter ranged between 3.2 cm (SI = 21m) and 6.0 cm (SI = 33m), and so it seems reasonable to assume that bark-stripping damage seldom occurs on such small trees because their stem will not be stiff or accessible enough (Gill et al, 2000).…”
Section: Model Assumptionsmentioning
confidence: 79%
See 3 more Smart Citations
“…We assumed that very few bark-stripping damage occurred in plantations younger than 8 years old (the simulations started in stands 8 years old) in line with several studies (Vospernik, 2006;Jerina et al, 2008;Gill et al, 2000;Konôpka et al, 2022). At 8 years old, the mean tree diameter ranged between 3.2 cm (SI = 21m) and 6.0 cm (SI = 33m), and so it seems reasonable to assume that bark-stripping damage seldom occurs on such small trees because their stem will not be stiff or accessible enough (Gill et al, 2000).…”
Section: Model Assumptionsmentioning
confidence: 79%
“…In addition, we assumed that only 5% of total bark stripping damage occurred in stands younger than 8 years and older than 36 years. This assumption seemed reasonable because most damage has been observed, in different independent studies, in stands 8-36 years old (Vospernik, 2006;Jerina et al, 2008;Gill et al, 2000;Konôpka et al, 2022). With these assumptions (distribution modes, proportion of damage in stands 8-36 years old), we computed the parameters of the two corresponding probability density functions ( f summer and f winter in Eq.…”
Section: Models Of Bark-stripping Damagementioning
confidence: 99%
See 2 more Smart Citations
“…This bark browsing occurred over three winter seasons: 2019/2020, 2020/2021, and 2021/2022. Previously, we conducted a similar study at the same site for common aspen (Populus tremula L.), common rowan (Sorbus aucuparia L.), and goat willow (Salix caprea L.; see Konôpka et al [31]). We found that the most intensive BATA es was in goat willow (14.5%), and the least intensive was in common rowan (5.1%).…”
Section: Bark Browsing (Stripping)mentioning
confidence: 99%